2013
DOI: 10.1177/0363546512471025
|View full text |Cite
|
Sign up to set email alerts
|

Allograft Salvage Procedure in Multiple-Revision Anterior Cruciate Ligament Reconstruction

Abstract: A 2-stage revision is an accepted option in cases of excessive tunnel enlargement and bone loss, especially on the femoral side, to achieve anatomic reconstruction. Nonanatomic over-the-top ACL reconstruction and lateral extra-articular plasty technique allow one to overcome difficult anatomic situations on the femoral side, permitting a 1-step surgery. The overall results obtained in this series are comparable with those of other ACL revision series. The higher rate of mild instability observed in our series … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
77
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 47 publications
(82 citation statements)
references
References 46 publications
5
77
0
Order By: Relevance
“…Five studies reported on a total of 50 males and 13 females, [12][13][14][15][16] with the remaining study of 151 patients composed of 60% males. 8 Two studies reported an average body mass index of 26.5 (n ¼ 151) 8 and 27.3 (n ¼ 15), respectively.…”
Section: Demographicsmentioning
confidence: 99%
See 4 more Smart Citations
“…Five studies reported on a total of 50 males and 13 females, [12][13][14][15][16] with the remaining study of 151 patients composed of 60% males. 8 Two studies reported an average body mass index of 26.5 (n ¼ 151) 8 and 27.3 (n ¼ 15), respectively.…”
Section: Demographicsmentioning
confidence: 99%
“…Of note, subsequent revisions resulted in greater chondral injury, and the location of the chondral damage tended to shift to the patellofemoral joint. 8 Of the 24 patients included in their study, Buda et al 12 reported diffuse cartilage lesions in 8 cases (International Cartilage Repair Society [ICRS] grades I [2], II [4], and III [2]) and focal osteochondral lesions in 4 cases (ICRS grades III [2] and IV [2]). Signs of focal chondral damage were further reported to be between 50% 12 and 67% 14 for evaluated subjects.…”
Section: Cartilage and Meniscus Statusmentioning
confidence: 99%
See 3 more Smart Citations